Cara Guru Mengembangkan Kecerdasan Spiritual kepada Anak - Mardiah Mardiah; Martina Napratilora; Abd Syahid; Syamsiah Nur (Al-Liqo: Jurnal Pendidikan Islam, 2022)
The problem is seen from the actions that are not good by children such as lack of manners, being brave to the teacher, saying harsh words and making fun of fellow friends which causes fights. This indicates a lack of spiritual intelligence in children. The formulation of the problem is how teachers develop spiritual intelligence to children. The aim is to study and analyze how teachers develop spiritual intelligence in children. The study of library research studies, and research results show that guiding children to find the meaning of life, getting used to thinking about giving something good, digging wisdom in every incident, developing five important exercises, namely happy to do good, happy to help people, find purpose in life, share the feeling of carrying a noble mission, and by having a good sense of humor, involving children in worship, enjoying beautiful natural scenery, visiting a grieving relative such as visiting a grieving relative, visiting a relative in an orphanage, visiting a sick relative, visiting a deceased relative die and visit relatives at the grave, through great stories, increase patience and gratitude, cultivate daily spiritual habits, discuss various issues from a spiritual perspective and give confidence that Allah is always watching.